Characteristics and Calculation of Surrounding Rock Pressure in Tunnel Lining With Backward Voids - Jingjian Bi; Zengchuan Kou; Ning Zhang; Jian Liu; Quanyi Xie; Gaohang Lv (Advances in Civil Engineering)
The distribution of surrounding rock pressure acting on the lining of a tunnel varies. This can cause stress concentration and accelerate lining deterioration that severely endangers the safety of tunnel operation. Owing to the complexity of the interaction between the lining and surrounding rock structure as well as the diversity of cavities, no straightforward method for calculating the surrounding rock pressure has been devised. In this study, a mechanical model of the pressure exerted by surrounding rock on the lining under different cavity conditions is established based on commonly used structural forms of highway tunnels. Moreover, the calculation formula for pressure is derived using numerical simulation and theoretical analysis. The research results are as follows: The distribution characteristics of surrounding rock pressure on the lining are the same under different cavity conditions and the load concentration phenomenon occurs at the cavity edge. As the cavity deflection angle increases, the difference in pressure concentration between both sides of the cavity increases. Formulas for calculating the concentrated load acting on the lining due to the surrounding rock under symmetrical and asymmetrical cavity distribution conditions are derived based on the limit equilibrium theory; their maximum errors are 8.9% and 7.4% compared with numerical simulation results. The influence of cavity span and deflection angle on the concentrated load exerted by the surrounding rock is analyzed using the calculation formula. However, under different deflection angles and circumferential spans of the cavity behind the lining, the change in the concentrated load acting on the lining due to the surrounding rock pressure is nonlinear. With an increase in the span of the cavity at different positions, the concentrated load exerted by the surrounding rock reaches its maximum and the load change law considerably varies.